Rancang Bangun Sistem Monitoring Konsumsi Daya Plts Listrik Hybrid On Grid (Studi Kasus BCA Kcu Madiun) - Oki, Moch Exca Candra Kharisma; Riyanto, Didik; Sulton Habibiy, Jawwad (SinarFe7, 2025)
Abstract - In an effort to reduce energy consumption and improve power efficiency, the installation of a Solar Power Plant (PLTS) has become a relevant solution for the commercial sector, including banking. The on-grid PLTS allows the generated energy to be directly fed into the public electricity grid, thereby reducing reliance on fossil fuels. The monitoring system for PLTS and grid power consumption utilizes voltage, current, and light (LDR) sensors to monitor performance in real-time. Sensor data is processed using the STM32F446RE microcontroller with an Arm Cortex-M4 core, which has digital signal processing and multi-ADC capabilities for high accuracy. This research aims to design an STM32-based power consumption monitoring system that can simultaneously monitor the energy flow from both PLTS and the grid, providing data for energy usage optimization and improving the operational efficiency of the on-grid PLTS system.